EFEITO DE DENSIDADE DE CRIAÇÃO SOBRE AS CARACTERÍSTICAS DE CARCAÇA DE FRANGOS DE CORTE ROSS 308 - SILVA, Maria Vitória; DE SOUZA, Andréia Fróes Galuci Oliveira; SILVA, Higor Jonathan de Oliveira; DA COSTA, Gabriela da Silva da; DOMINGUES, Elyan Carlos Da Silva; MARQUES, Ana Leticia Ribeiro (ANAIS DO ENIC, 2023)
-